2020
DOI: 10.1121/10.0001585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consonantal constrictions on voice quality

Abstract: A speech production experiment with electroglottography investigated how voicing is affected by consonants of differing degrees of constriction. Measures of glottal contact [closed quotient (CQ)] and strength of voicing [strength of excitation (SoE)] were used in conditional inference tree analyses. Broadly, the results show that as the degree of constriction increases, both CQ and SoE values decrease, indicating breathier and weaker voicing. Similar changes in voicing quality are observed throughout the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This was to control as much as possible for the role of phrasal position on laryngeal voicing. Target sounds that were described as (possibly) having supra-laryngeal constriction were excluded, as such constriction promotes devoicing (Esling et al 2019) and lowers voicing intensity (Chong et al 2020, Garellek 2020). Thus, we excluded epiglottal stops and fricatives [ʡ ʜ ʢ], as well as [ʔ h] if they were reported to have pharyngealization or velarization, or sounded that way to us (due to trilling and/or lowered vowel quality).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was to control as much as possible for the role of phrasal position on laryngeal voicing. Target sounds that were described as (possibly) having supra-laryngeal constriction were excluded, as such constriction promotes devoicing (Esling et al 2019) and lowers voicing intensity (Chong et al 2020, Garellek 2020). Thus, we excluded epiglottal stops and fricatives [ʡ ʜ ʢ], as well as [ʔ h] if they were reported to have pharyngealization or velarization, or sounded that way to us (due to trilling and/or lowered vowel quality).…”
Section: Methodsmentioning
confidence: 99%
“…As such, SoE measures the relative amplitude of voicing, independent of noise in the signal (Murty & Yegnanarayana 2008). This measure has been used in studies of the role of vocal tract constriction (Mittal, Yegnanarayana & Bhaskararao 2014, Chong et al 2020) and source aspiration or glottalization on the amplitude of voicing (Faytak et al 2020, Garellek 2020). SoE was calculated using VoiceSauce (Shue et al 2011) over the labeled intervals of aspiration and glottalization.…”
Section: Methodsmentioning
confidence: 99%
“…Syllable stress was also coded and included in the models, following Bolyanatz (Forthcoming) who showed that stress in Chilean Spanish co-occurs with voice quality variation. The phonological segment preceding and following the vowel nucleus was coded to account for prosodic boundary effects and other potential context effects (Chong et al 2020). The predictor of speaker age was also included given that some studies have found relationships between acoustic measures, such as F0 and HNR, and age; these studies tend to find that HNR and F0 tend to decrease as speakers age (Ferrand 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One plausible source of this effect, which should be considered in future research, is that modal voicing is lost more readily under narrower supralaryngeal constrictions, which encourage a fast buildup of intra-oral pressure (Stevens 1998; Solé 2010; Chong et al. 2020). Nasals and prenasalized consonants, which vent airflow through the open velopharyngeal port, may thus be less prone to anticipatory loss of non-modal voicing, even given a similar extent and timecourse of vocal fold spreading (e.g.…”
Section: Discussionmentioning
confidence: 99%